Prevenient Grace (Anugerah Pendahulu) Sebagai Teras Keselamatan dalam Doktrin Keselamatan John Wesley - Manimpan Hutasoit (Majalah Ilmiah METHODA, 2026)
The doctrine of Prevenient Grace (Anugerah Pendahulu) is one of the distinctive features of John Wesley’s soteriology, affirming that the initiative of salvation originates entirely from God. This grace operates antecedently in every person, awakening an awareness of sin, restoring the capacity to respond to God’s call, and opening the way to repentance, justification, and sanctification. This study aims to analyze Prevenient Grace as the core of salvation in John Wesley’s doctrine of salvation. The research employs a qualitative method with a library-study approach to Wesley’s primary works and the literature on Wesleyan theology. The findings indicate that Prevenient Grace constitutes the foundation of the entire salvific process, insofar as God’s grace precedes every human response without removing the human freedom to accept or reject it. The doctrine thus underscores a balance between divine sovereignty and human responsibility.